An Ethical Framework for Global Psychiatry - Craig L. Katz; Timothy P. Lahey; Hilary T. Campbell (Ubiquity Press, 2014)
Existing literature addresses the ethical considerations of global health work and how medical school curricula can help prepare students for them, but little has been written regarding an ethical approach to global psychiatry. In this paper we summarize prominent ethical issues that arise in global health psychiatry in order to provide a foundation for a framework in global health psychiatry. These issues include obtaining informed consent in the face of language barriers, diagnosing and treating for mental illnesses while navigating communities where such conditions are heavily stigmatized, and justifying the cessation of proving care to current patients for the sake of providing care to new patients abroad. To help prepare psychiatrists and students for work that engages these issues, we propose a multi-step process to assist the practicing global psychiatrist in recognizing ethical dilemmas and evaluating potential courses of action based on their respective ethical merits.